(untitled) (Zaporizhzhia Historical Review, 2021)
The question of relationship of M.V. Gogol’s ancestors with the representatives of Cossack starshyna (higher officers) of the Myrgorod regiment is being considered. The influence of this surrounding upon the writer’s creative activity is being investigated.